2023
DOI: 10.1186/s12912-023-01264-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing perceptions about critical thinking, motivation learning strategies in online psychiatric and mental health nursing education among Egyptian and Saudi undergraduate nursing students

Abstract: Background The pandemic context prompts nursing students to be involved in online learning. Researchers indicated that critical thinking develops through the learning process, but the link between critical thinking and online learning in nursing does not have sufficient evidence. Aim of Study This research examines student perceptions about critical thinking, motivation, and learning strategies in online psychiatric nursing education among nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The results show that innovative approaches foster student involvement, independent learning and practical application. In particular, collaborative learning improves students' writing fluency, coherence and organization (AlOtaibi et al ., 2023). According to the study, implementing cutting-edge teaching techniques is consistent with the interactive and communicative qualities of the German language.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results show that innovative approaches foster student involvement, independent learning and practical application. In particular, collaborative learning improves students' writing fluency, coherence and organization (AlOtaibi et al ., 2023). According to the study, implementing cutting-edge teaching techniques is consistent with the interactive and communicative qualities of the German language.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies often employ direct instruction, textbook-based learning and drills (Jingxuan et al, 2023;Yawman and Appiah-Kubi, 2018). Research conducted by AlOtaibi et al (2023) in Saudi Arabian international schools suggested that traditional teaching methods can be effective in teaching the fundamentals of German writing, such as sentence structure and basic vocabulary. However, these approaches are often criticized for their limited engagement and creativity, which may not adequately address the diverse needs of students, particularly in the context of international schools (Al-Ahdal and Abduh, 2021).…”
Section: Literature Review 21 Traditional Teaching Strategiesmentioning
confidence: 99%
See 3 more Smart Citations